Cyclorraphan yolk proteins and lepidopteran minor yolk proteins originate from two unrelated lipase families. - Hens, K; Lemey, P; Macours, N; Francis, C; Huybrechts, R (2004)
Vitellogenins, cyclorraphan yolk proteins and lepidopteran minor yolk proteins are three classes of female-specific proteins that serve as an embryonic nutritional store. Similarity to vertebrate lipid-binding proteins was established for vitellogenins and yolk proteins, vitellogenins being related to apolipoprotein B and yolk proteins to lipases. Recently, similarity between yolk proteins and minor yolk proteins was reported and it was suggested that yolk proteins are more related to minor yolk proteins than to vertebrate lipases. In this study, we cloned five additional yolk proteins from the grey fleshfly Neobellieria bullata, formerly known as Sarcophaga bullata. We used this sequence data, combined with sequence data retrieved from the NCBI protein database to evaluate the yolk protein-lipase and the yolk protein-minor yolk protein relationship. We found no similarity between yolk proteins and minor yolk proteins, but we showed that yolk proteins are related to a family of lipases containing vertebrate hepatic and pancreatic lipases while minor yolk proteins are related to a family of lipases containing vertebrate gastric and lingual lipases. The fact that three different classes of yolk storage proteins show similarity to three different classes of vertebrate lipid-binding proteins strongly suggests that this lipid-binding feature is important for insect yolk storage proteins.